2016
DOI: 10.3892/ol.2016.4731
|View full text |Cite
|
Sign up to set email alerts
|

Predicting associations between microRNAs and target genes in breast cancer by bioinformatics analyses

Abstract: Abstract. Breast cancer is the leading type of cancer among females. However, the association between microRNAs (miRNAs) and target genes in breast tumorigenesis is poorly studied. The original data set GSE26659 was downloaded from the Gene Expression Omnibus, and then the differentially expressed miRNAs among 77 breast cancer patients and 17 controls were identified using the Limma package in R software. Furthermore, breast cancer-related differentially expressed miRNAs were selected from a human miRNA diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 34 publications
(30 reference statements)
2
9
0
Order By: Relevance
“…BCa patients are likely to develop tumor recurrence and metastasis after surgical treatment [18]. In recent years, miRNAs in BCa research have attracted increasing research attention [7,19], for example studies on the interaction between miRNA with related target genes and the regulative role of signaling pathways revealed the critical effects of miRNAs on tumors [20,21]. Thus, discovering clinical targets indicating the prognosis of BCa may contribute to the treatment of BCa.…”
Section: Discussionmentioning
confidence: 99%
“…BCa patients are likely to develop tumor recurrence and metastasis after surgical treatment [18]. In recent years, miRNAs in BCa research have attracted increasing research attention [7,19], for example studies on the interaction between miRNA with related target genes and the regulative role of signaling pathways revealed the critical effects of miRNAs on tumors [20,21]. Thus, discovering clinical targets indicating the prognosis of BCa may contribute to the treatment of BCa.…”
Section: Discussionmentioning
confidence: 99%
“…Using microarray and PCR, we found a significant downregulation of miR-143 and miR-145 in malignant tumors compared to normal tissue, which is in line with previously published studies in breast cancer [ 29 ā€“ 31 ] and other tissues, especially colorectal carcinomas [ 32 ]. However, in our study the results were also verified by ISH, which added interesting data on the cellular and subcellular location of these miRNAs in benign and malignant breast tissue.…”
Section: Discussionsupporting
confidence: 91%
“…It reported that microRNA feedback loops induced apoptosis in breast cancer and colorectal cancer 14,15. A study showed that 13 miRNAs were expressed in breast cancer tissues and serum, but they showed variations.16 Thus, miRNAs may be released into the blood via breast cancer cells and be involved in different molecular mechanisms in tissues and serum. There were 1096 patients with breast cancer and 112 controls in the TCGA cohort (Figure 1A and B).…”
Section: Discussionmentioning
confidence: 99%